Phronesis as Professional Knowledge Practical Wisdom in the Professions - Kinsella, Elizabeth Anne.; Pitman, Allan; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Phronesis is the Aristotelian notion of practical wisdom. In this collected series, phronesis is explored as an alternate way of considering professional knowledge. In the present context dominated by technical rationalities and instrumentalist approaches, a re-examination of the concept of phronesis offers a fundamental re-visioning of the educational aims in professional schools and continuing professional education programs. This book originated from a conversation amongst an interdisciplinary group of scholars from education, health, philosophy, and sociology, who share concerns that something of fundamental importance – of moral signi?cance – is missing from the vision of what it means to be a professional. The contributors consider the ways in which phronesis offers a generative possibility for reconsidering the professional knowledge of practitioners. The question at the centre of this inquiry is: “If we take phronesis seriously as an organising framework for professional knowledge, what are the implications for professional education and practice?” A multiplicity of understandings emerge as to what is meant by phronesis and how it might be reinterpreted, understood, applied, and extended in a world radically different to that of the progenitor of the term, Aristotle. For those concerned with professional life this is a conversation not to be missed.
Keywords: Education; Education, general